2008
DOI: 10.3354/meps07633
|View full text |Cite
|
Sign up to set email alerts
|

Sea temperature variations mediate annual changes in the diet of Australian fur seals in Bass Strait

Abstract: Using a 9-yr data set, we investigated annual fluctuations in the diet of an apex predator, the Australian fur seal Arctocephalus pusillus doriferus. At Seal Rocks (northern Bass Strait), home to 25% of the entire species population, we assessed diet through collections (1997 to 2006) of scat and regurgitate samples. We identified prey remains of 42 fish taxa and 7 cephalopod taxa. Only crustaceans that were fish parasites or fish prey (amphipods and isopods) were found; no birds were identified in the samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(94 citation statements)
references
References 45 publications
1
89
4
Order By: Relevance
“…In northern Bass Strait, interannual fluctuations in sea-surface temperature have been correlated with broad fluctuations in the prey composition of Australian fur seals (Kirkwood et al, 2008). The increase in Brucella prevalence between 2003 and 2005 corresponded with a protracted period of cooler-thanaverage sea surface temperatures and higher-than-average proportions of the fish redbait (Emmelichthys nitidus) in the diet of Australian fur seals in northern Bass Strait.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In northern Bass Strait, interannual fluctuations in sea-surface temperature have been correlated with broad fluctuations in the prey composition of Australian fur seals (Kirkwood et al, 2008). The increase in Brucella prevalence between 2003 and 2005 corresponded with a protracted period of cooler-thanaverage sea surface temperatures and higher-than-average proportions of the fish redbait (Emmelichthys nitidus) in the diet of Australian fur seals in northern Bass Strait.…”
Section: Discussionmentioning
confidence: 99%
“…The pupping season of Australian fur seals is synchronized and occurs between mid-November and mid-December (Gibbens and Arnould, 2009 To investigate possible spatial differences in antibody prevalence, pups from three other Australian fur seal colonies, The Skerries (37u459S, 149u319E), Seal Rocks (38u309S, 145u109E) and Lady Julia Percy Island (38u429S, 142u009E), were sampled between late December 2007 and late January 2008. This sampling was conducted concurrently with a mark-recapture study (Kirkwood et al, 2010).…”
Section: Blood Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…redbait Emmelichthys nitidus, barracouta Thyrsites atun, jack mackerel Trachurus declivis, red cod Pseudophysis bachus and leatherjacket (family Monocanthidae), as well as of Gould's squid Nototodarus gouldi (Gales et al 1993, Gales & Pemberton 1994, Hume et al 2004, Page et al 2005, Littnan et al 2007, Kirkwood et al 2008. These studies, however, have all demonstrated that Australian fur seals regularly consume a wide variety of prey (43 to 49 species) and that the species is a generalist predator (Littnan et al 2007).…”
Section: Abstract: Australian Fur Seal · Otariid · Stable Isotopes ·mentioning
confidence: 99%
“…From analysis of faecal samples collected over a 9 yr period, Kirkwood et al (2008) documented a major inter-annual shift in Australian fur seal diet composition. A multi-year increase in the frequency of occurrence of redbait coincided with decreases in red cod and barracouta, as well as a reduction in the size of Gould's squid.…”
Section: Abstract: Australian Fur Seal · Otariid · Stable Isotopes ·mentioning
confidence: 99%